Cancer Incidence Rates among Iranian immigrants in Sweden, a Population-Based Retrospective Cohort Study - Omid Beiki; Kazem Zendehdel; Shahram Bahmanyar; Mohammad Ali Mohagheghi; Par Sparen; Alireza Mousavi Jarrahi; Sara Keshtkari; Azin Nahvijou; Zahra Sedighi; Leila Shademan; Olof Nyren; Tahereh Moradi (Basic & Clinical Cancer Research, 2014)
Introduction: Migrant studies may provide valuable clues to the etiology of chronic diseases such as cancer. We conducted a migrant study to examine cancer incidence among Iranian immigrants in Sweden. Methods: A cohort of Iranian immigrants in Sweden in 1960-2004 was followed through record linkages with Swedish registers of cancer, death, and migration. We compared Age-Standardized Incidence Rates (ASRs) with corresponding ASRs in Tehran and Sweden and estimated Standard Rate Ratios with 95% confidence intervals (CI). In addition, ASRs were stratified by follow-up time. Results: In total 1,041 cancers occurred among 60,718 Iranian immigrants. The ASRs for all cancers combined were 182.3 and 175.5 per 100,000 person-years among men and women, respectively. For men, this rate was slightly and non-significantly higher than in Iran, while for women the excess (24%) was statistically significant. However, their ASRs were significantly lower than those for native Swedes: men had 37% (95% CI 27-47%) and women 35% (95% CI 33-37%) lower ASRs.Â  Compared to male Iranians living in Tehran, ASRs of esophageal and gastric cancer were lower while ASRs of colorectal and prostate cancer were higher, and both of the latter increased with time since immigration. In women, the ASR of non-melanoma skin cancer was lower and that of breast cancer higher and increasing. Conclusion: In male first-generation immigrants, incidence rates of esophageal, gastric, colorectal, and prostate cancer change in the direction of prevailing rates in Sweden, likely due to changes in exposure to environmental risk factors. A similar adjustment occurs for breast and non-melanoma skin cancer among female immigrants.